2016
DOI: 10.18632/oncotarget.10374
|View full text |Cite
|
Sign up to set email alerts
|

FNDC3B promotes cell migration and tumor metastasis in hepatocellular carcinoma

Abstract: Recurrence and metastasis are common in hepatocellular carcinoma (HCC) and correlate with poor prognosis. We investigated the role of fibronectin type III domain containing 3B (FNDC3B) in HCC metastasis. Overexpression of FNDC3B in HCC cell lines enhanced cell migration and invasion. On the other hand, knockdown of FNDC3B using short-hairpin RNA reduced tumor nodule formation in both intra- and extra-hepatic metastasis. High levels of FNDC3B were observed in metastatic HCCs and correlated with poor patient sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 37 publications
4
41
0
Order By: Relevance
“…FNDC3B , also known as FAD104 (factor for adipocyte differentiation 104), is located at 3q26, and is amplified in more than 20% of human tumors 24,25 . Recently, FNDC3B was found to serve as an oncogene and it can promote tumorigenesis and metastasis in various cancer types 24‐28 . FNDC3B can promote cell migration and metastasis by cooperating with annexin A2 (ANXA2) in hepatocellular carcinoma 26 .…”
Section: Discussionmentioning
confidence: 99%
“…FNDC3B , also known as FAD104 (factor for adipocyte differentiation 104), is located at 3q26, and is amplified in more than 20% of human tumors 24,25 . Recently, FNDC3B was found to serve as an oncogene and it can promote tumorigenesis and metastasis in various cancer types 24‐28 . FNDC3B can promote cell migration and metastasis by cooperating with annexin A2 (ANXA2) in hepatocellular carcinoma 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have con rmed that FNDC3B promotes tumor progression. Lin et al found that FNDC3B enhances the migration and metastasis of hepatocellular carcinoma cells by binding to annexin A2 (ANXA2) through the FNIII1-4 domain [14]. Cai et al con rmed that FNDC3B increases the proliferation of liver cancer cells by inducing epithelial to mesenchymal transition (EMT) to activate the PI3K / AKT, Rb1 and TGF-β pathways [28].…”
Section: Discussionmentioning
confidence: 99%
“…Fibronectin type III domain containing 3B (FNDC3B), is a protein of the FNDC3 family that includes FNDC3A, FNDC3B and FNDC3C, also known as factor for adipocyte differentiation 104 (FAD104), it contains a proline-rich region, and 9 bronectin type III structures domain and a transmembrane region, and is a regulator of adipocyte and osteoblast differentiation [8][9][10][11][12]. Fibronectin type III (FNIII) domain of FNDC3B serves as a tail sheath, integrates with different proteins, and plays an important role in cell adhesion and growth signaling [9,13,14]. Homozygous disruption of FNDC3B causes mice to die at birth from abnormalities in the lungs [14,15], and has a signi cant effect on the adhesion, proliferation and migration of mouse embryonic broblasts [9,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that most of the miR-215-targeted genes have oncogenic properties which corresponds to the tumor suppressive role of Pax-5 in breast cancer cells (41)(42)(43)(44)(45)(46). For example, Fibronectin type III domain containing 3B gene (FNDC3B) located at the 3q26 locus is amplified in 20% of tumors and plays an oncogenic role in many cancers (41,47). Additionally, activated leukocyte cell adhesion molecule (ALCAM) is implicated in cell to cell interactions and inhibits breast cancer apoptosis (43).…”
Section: Discussionmentioning
confidence: 99%